Unravelling the relationship between perceived values-congruence with organizational change readiness: A moderated mediation model - Deng, Jinzhao; Cheng, Zhihui; Qi, Siqi; Deng, Rich (Frontiers in Psychology, 2023)
Recent studies have demonstrated that organizations often fail to execute organizational changes effectively due to a lack of their employees’ organizational change readiness (OCR). However, the absence of employees’ OCR is rooted in whether their values align with their organizations. The research aims to clarify when and why employees’ perceived values-congruence with their organizations, supervisors, and workgroups (PVC-O, PVC-S, and PVC-G) helps stimulate their organizational change readiness (OCR). Specifically, it Integrates the self-categorization theory and social information processing theory and proposes a moderated mediation model to investigate the roles of perceived insider status (PIS) and the quality of change communication (QCC). This study gathered a valid sample of 252 employees from six Chinese companies at three different time points, and performed the structural equation modeling and multiple regression to test the proposed research model. The results demonstrate that PVC-O, PVC-S, and PVC-G are all positively related to employees’ PIS, which further promotes their readiness for organizational change. Additionally, QCC strengthens not only the positive effect of employees’ PVC-O and PVC-G (except for PVC-S) on PIS but also the indirect effects of PIS. This study offers valuable implications for practitioners implementing their organizational change practices in China. Moreover, this study can contribute to the organizational change literature by uncovering the underlying mechanism between perceived values-congruence and employees’ OCR in the light of the person-environment interaction.